Teacher Recruitment: a Bibliometric Analysis and Visualization of Emerging Trends, Challenges and Applications - Mochamad Nashrullah; Fitrotul Choiriyah; Darto; Gaguk Tri Prasetyo; Budi Purwoko (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to analyze research trends on teacher recruitment through a bibliometric study and explore how Indonesian researchers contribute to the Scopus database from 2013 to 2023. The sample consisted of 287 documents. The results showed that scientific publications on teacher recruitment have increased. The United States contributed 125 documents, while the institution that contributed the most articles was the UCL Institute of Education from the UK. Visualization of research trends using the VOS Viewer application resulted in 7 main clusters: (1) Teacher recruitment related to teacher retention, education policy, and teacher preparation (2) Teacher recruitment related to teacher education, retention, teacher quality, and teacher development, (3) Teacher recruitment related to a teacher shortage, (4) Teacher recruitment related to teacher training (5) Teacher recruitment related to career choice, (6) Teacher recruitment related to teaching, education, curriculum, (7) Teacher recruitment related to motivation, teacher colleges, students and professional development. The findings of this study can help researchers on the topic of teacher recruitment globally and recommend further research on teacher recruitment.